2018
DOI: 10.1021/acs.jchemed.7b00410
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Simple Wax Screen-Printing Paper-Based Analytical Devices To Demonstrate the Concept of Limiting Reagent in Acid–Base Reactions

Abstract: In this article, a low-cost, simple, and rapid fabrication of paper-based analytical devices (PADs) using a wax screen-printing method is reported here. The acid–base reaction is implemented in the simple PADs to demonstrate to students the chemistry concept of a limiting reagent. When a fixed concentration of base reacts with a gradually increasing concentration of acid, a dramatic demonstration allows students to discover the limiting reagent by naked eyes observing the color change from phenolphthalein as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Dungchai et al wax patterned chromatography paper and subsequently melted the wax using a hot plate in three dimensions (3D) of the paper in order to form hydrophobic barriers. Namwong et al used a home hair dryer to melt the wax into the paper [ 39 ]. In another study, wax microstructures were printed on a nitrocellulose membrane, and then baked to enable the printed wax to penetrate the wax and create hydrophobic channels in the device [ 29 ].…”
Section: Fabrication and Printingmentioning
confidence: 99%
“…Dungchai et al wax patterned chromatography paper and subsequently melted the wax using a hot plate in three dimensions (3D) of the paper in order to form hydrophobic barriers. Namwong et al used a home hair dryer to melt the wax into the paper [ 39 ]. In another study, wax microstructures were printed on a nitrocellulose membrane, and then baked to enable the printed wax to penetrate the wax and create hydrophobic channels in the device [ 29 ].…”
Section: Fabrication and Printingmentioning
confidence: 99%
“…Recently, paper-based analytical devices (PADs) have garnered significant attention as chemical education tools and analytical tools. To date, many educational applications have been described, including in the areas of analytical chemistry, organic synthesis, , materials chemistry, and electrochemistry. , PADs have many advantages, such as on-site usage, cost-effectiveness, ease of fabrication, good portability, and user-friendliness . Furthermore, image analysis-based colorimetry combined with smartphone devices allows straightforward detection, which requires no dedicated instruments. , However, these PAD-based experimental systems are intended for use in laboratories because they require special experimental equipment, such as micropipettes.…”
Section: Introductionmentioning
confidence: 99%
“…As for hydrophobic agents, PDMS and wax have been proposed quite comprehensively for the fabrication of μPADs 21 24 , 26 , especially the latter, due to its affordability and availability. However, reports have indicated that μPADs fabricated using wax are inflexible and impaired under bending stress 25 .…”
Section: Introductionmentioning
confidence: 99%